Degradation of low-density polyethylene by a novel strain of bacteria isolated from the plastisphere of marine ecosystems - F.A. Febria; A. Syafrita; A. Putra; H. Hidayat; C. Febrion (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Low-density polyethylene is one of the dominant recalcitrant plastic pollutants in the ocean, thus causing complicated problems. Biodegradation is an efficient, environmentally friendly, and sustainable option to overcome these problems. This study aims to quantitatively and qualitatively analyze the ability of marine bacterial isolates to degrade low-density polyethylene plastic.METHODS: Bacteria were isolated from plastic samples using serial dilution technique and inoculated on media containing low-density polyethylene powder. Bacterial degradation ability was analyzed quantitatively based on weight loss percentage and energy-dispersive X-ray spectroscopy values, as well as qualitatively based on changes in physical and chemical structures using Scanning Electron Microscopy and Fourier transform infrared spectroscopy. Meanwhile, bacterial isolates were identified based on gene sequence and phylogenetic analyses.FINDINGS: Four bacterial isolates were isolated from low-density polyethylene plastic samples. Quantitative analysis found that the low-density polyethylene film experienced weight loss up to 10-15 percent during 35 days of incubation, with a maximum daily weight loss rate of 0.004 milligrams per day, meaning that the four bacterial isolates have the potential to degrade plastic. Meanwhile, qualitative analysis based on Scanning Electron Microscope observations revealed changes in the physical structure of the film surface in the form of a rough surface, formation of holes, and breakdown into clumps across the film surface. Variations in these changes were tested. In the control, no changes occurred and the film surface remained flat and smooth. Conversely, the results of the energy dispersive X-ray spectroscopy spectrum analysis showed that the low-density polyethylene film broke down into smaller fragments, characterized by a decrease in mass from 98.51 percent to 98.23 percent. Fourier transform infrared observations showed variations in transmittance and wavenumbers, indicating changes in chemical bonds or functional groups in the low-density polyethylene film which caused it to become brittle and break down into smaller fragments with a lower molecular weight, making it easier for bacteria to digest. The results of the gene sequence analysis identified four bacterial isolates, namely Lysinibacillus sp. IBP-1, Bacillus sp. IBP-2, Bacillus paramycoides IBP-3, and Bacillus cereus IBP-4. Based on the quantitative and qualitative analyses, the ability of the bacterial isolates to degrade low-density polyethylene film was shown in the following order: Bacillus paramycoides IBP-3 > Bacillus cereus IBP-4 > Lysinibacillus sp. IBP-1 > Bacillus sp. IBP-2.CONCLUSION: All four marine bacterial isolates can use low-density polyethylene as the sole carbon source. Based on quantitative and qualitative analyses, Bacillus paramycoides IBP-3 has the best potential for degrading low-density polyethylene film. This study provides information on potential bacterial isolates that can be developed to control low-density polyethylene plastic waste.